METOPROLOL-INDUCED LIVER INJURY AND THE HEPATOPROTECTIVE ROLE OF VITAMIN E IN RABBITS - MAYSAA BANAY ZUBAIRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to investigate the hepatotoxicity of metoprolol and find a prophylactic way to protect the liver through the use of Vitamin E. Methods: A total of 18 male rabbits were divided randomly into three groups, with six in each group. Group I (control) received corn oil, Group II was treated with metoprolol (20 mg/kg), and Group III was treated with Vitamin E (175 mg/kg) 30 min before metoprolol treatment. All treatments were given orally and daily for 14 days; animals were sacrificed at day 15. Biochemical parameters were estimated, and the liver was used for histopathological examinations. Results: Histopathological changes of liver injury were found in all metoprolol-treated rabbits, while these changes were minimized in all rabbits who were given Vitamin E. Serum liver function tests and malondialdehyde (MDA) were significantly elevated after metoprolol treatment and returned close to the control value on prior treatment with Vitamin E. Serum MDA, aspartate aminotransferase, and alanine aminotransferase were significantly decreased following treatment with Vitamin E. Conclusion: Vitamin E may have a hepatoprotective effect against metoprolol-induced liver injury in rabbits.